Sistem Pemberian Nutrisi Pada Tanaman Hidroponik Menggunakan Metode Fuzzy Berbasis Arduino - Asrori, Muhamad; Murdani, M Harist (Journal of System Engineering and Technological Innovation, 2023)
Hydroponics is a method of farming using water as a substitute for soil. The nutrient solution is the most important thing to replace soil nutrients needed by plants. To maintain nutrition so that it remains on the verge of normal requires routine nutritional monitoring. Therefore, to facilitate monitoring of plants and maintain optimal nutritional value, through this research an NFT-based Automatic Hydroponic Plant Nutrient Feeding System was developed. The pH sensor and TDS sensor check the levels of nutrients in plants, the solenoid valve controls the nutrients released. Arduino UNO is used as a system control tool with the nutritional time value calculation method generated using the Fuzzy Logic method. Making this system aims to facilitate nutritional care with accurate results.